La Experiencia Comunicativa del “entorno educativo” (2017)
The next text shows the communicative practices between teachers and students that emerges from Antioquia, Copacabana, San Rafael School, seventh grade. It is a qualitative research because it starts by using assumptions due to the subject’s capacity to observe and describe reality; also to be aware of the multiple possibilities to interpretate the social structures focusing in the social- critical and hermeneutic perspectives having into an account changes and situations that can link the researcher and the subject of study. The analysis results helped us to assert that teachers and students share their lives in different spaces inside the school, but the classroom is unique. It is a space where people can interact closer to each other; people interweave speeches, doubts, intentions and knowledge. Also inside the classroom they are lectures of communicative power – who has the main speech-, constant fights for whom should be listened and whom should be heard; and in this paraphernalia will win the one who has the most convincing speech. So the communicative interactions between teachers and students are uncountable. The classroom is a place charged and full of meanings, constructions and interactions; an environment with silent resistances eager to be heard, but most of all a place full of life